2023
DOI: 10.21070/ijler.v19i0.908
|View full text |Cite
|
Sign up to set email alerts
|

Taxpayer Awareness and Knowledge Boost Tax Compliance during COVID-19: Role of Socialization

Abstract: The aim of this study is to investigate the influence of taxpayer attitude, awareness, and tax knowledge on tax compliance during the COVID-19 pandemic, with tax socialization as a moderating variable. The study focuses on 33 businesses registered under the Indonesian Contractor and Mechanical Association (AKLI) Sidoarjo branch in 2022, using purposive sampling criteria. The SmartPLS (Partial Least Square) analysis was used to analyze the data. The results indicate that taxpayer attitude does not significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…A social media campaign with a famous person promoting tax payment can help more people decide to pay taxes, but it works better in an integrated society and when there is no big gap between rich and poor. Shoffan & Ernandi (2023) investigated the influence of taxpayer attitude, awareness and tax knowledge on tax compliance among 33 businesses registered under the Indonesian Contractor and Mechanical Association during the COVID-19 pandemic, with tax socialization as a moderating variable. The study found that the way taxpayers feel about taxes does not really change whether they follow tax rules or not.…”
Section: Social Influence Theorymentioning
confidence: 99%
“…A social media campaign with a famous person promoting tax payment can help more people decide to pay taxes, but it works better in an integrated society and when there is no big gap between rich and poor. Shoffan & Ernandi (2023) investigated the influence of taxpayer attitude, awareness and tax knowledge on tax compliance among 33 businesses registered under the Indonesian Contractor and Mechanical Association during the COVID-19 pandemic, with tax socialization as a moderating variable. The study found that the way taxpayers feel about taxes does not really change whether they follow tax rules or not.…”
Section: Social Influence Theorymentioning
confidence: 99%